2004
DOI: 10.1055/s-2004-832677
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacology of the Anxiolytic Drug Opripramol, a Sigma Site Ligand

Abstract: Although opipramol is structurally related to imipramine, it does not represent a tricyclic antidepressant drug as it does not inhibit the neuronal uptake of norepinephrine and/or serotonin. Unlike imipramine it is a rather potent sigma ligand with modest subclass selectivity which is similar in vitro as well as ex vivo. Opipramol is active in several behavioural paradigms indicative of anxiolytic properties at doses (1-10 mg/kg), which are also needed to occupy sigma binding sites. Somewhat higher doses (10-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 27 publications
1
24
0
2
Order By: Relevance
“…It has been shown that some clinically used centrally active drugs (e.g. pentazocine, haloperidol, fluvoxamine, donepezil, opipramol) also display high affinity to 1 receptors [1][2][3]. Therefore 1 ligands are considered as potential useful drugs for the treatment of several psychiatric disorders, including depression, psychosis, anxiety, as well as alcohol and cocaine abuse.…”
Section: Introductionmentioning
confidence: 98%
“…It has been shown that some clinically used centrally active drugs (e.g. pentazocine, haloperidol, fluvoxamine, donepezil, opipramol) also display high affinity to 1 receptors [1][2][3]. Therefore 1 ligands are considered as potential useful drugs for the treatment of several psychiatric disorders, including depression, psychosis, anxiety, as well as alcohol and cocaine abuse.…”
Section: Introductionmentioning
confidence: 98%
“…[1] Moreover, derivatives such as metapramine (II) also present analgesic properties, [2] whereas opipramol (V) shows an anxiolytic profile. [3] Besides other activities, some of these tricyclic structures are known as receptor antagonists (VI). Oxcarbazepine (OXC, Trileptal, VII) represents the first narrow-spectrum antiepileptic drug (AED) and more recently was used as a monotherapy for the treatment of partial seizures in adults.…”
mentioning
confidence: 99%
“…It binds 7-8 times stronger to the sigma-1 receptor compared to the sigma-2 receptor with antagonistic properties. Although the exact intracellular effects of opipramol remain unclear, data obtained by Mueller et al [20] allow the conclusion that interaction with the sigma site is involved in the anxiolytic and antidepressant effects of opipramol. However, a contribution of its weaker antagonistic effects to the dopaminergic (D 2 ) receptor and the serotonergic (5-HT 2a ) receptor cannot be totally ruled out.…”
Section: Introductionmentioning
confidence: 95%
“…However, a contribution of its weaker antagonistic effects to the dopaminergic (D 2 ) receptor and the serotonergic (5-HT 2a ) receptor cannot be totally ruled out. Its low affinities and antagonistic properties to the muscarinergic receptors and the ␣ -adrenergic receptors is associated with only moderate cardiovascular effects [20][21][22] . The antihistaminergic properties (H 1 receptor antagonist) can explain sedative and hypnotic effects.…”
Section: Introductionmentioning
confidence: 99%